2014
DOI: 10.1108/lodj-04-2012-0054
|View full text |Cite
|
Sign up to set email alerts
|

The relationships amongst leader-member exchange, perceived organizational support, affective commitment, and in-role performance

Abstract: Purpose-The purpose of this paper is to examine whether leader-member exchange (LMX) and perceived organizational support (POS) have interactive effects on affective commitment to the organization. The utility of Social Exchange Theory for explaining workplace attitudes and behaviors in non-Western settings has been questioned. Another objective is to test the hypotheses, which are based on Social Exchange Theory, within a Chinese context. Design/methodology/approach-Cross-sectional, self-report data on LMX, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 80 publications
(102 reference statements)
7
81
0
12
Order By: Relevance
“…We tend to perceive that POS provides a cherished and effective environment to motivate employees to continue their IB. Furthermore, our results support findings from previous empirical research [47,67,[126][127][128], which suggests that POS is positively associated with employees' IB and affective commitment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We tend to perceive that POS provides a cherished and effective environment to motivate employees to continue their IB. Furthermore, our results support findings from previous empirical research [47,67,[126][127][128], which suggests that POS is positively associated with employees' IB and affective commitment.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, Eisenberger et al and Liu, [63,72] suggested that when the employees recognize their organization is supportive and take care of them, then they will more likely be committed towards the organization. Furthermore, previous empirical research proposed that POS positively influences employees' affective commitment and innovative work behavior [47,67,126,127]. Along the lines of SET, a high POS is associated with better mood, self-esteem, behaviors, and positive attitudes; low POS is related to a depressed mood, lower self-esteem, behaviors, and attitudes that are not beneficial for achieving organizational goals [72,130].…”
Section: Discussionmentioning
confidence: 97%
“…That is why having qualified faculty / lecturers and students, if not balanced with good system and organizational support, the competitiveness of such educational institutions will not be high. In line with the research by Casimir et al (2014) and Allen & Shanock (2013) showed that organizational support to employees will increase the commitment and performance of these employees.…”
Section: Having Good Intangible Assetssupporting
confidence: 62%
“…Therefore, by enhancing AC, POS should lead to increased performance. Accordingly, AC has been found to mediate the association between POS and performance (Casimir, Ng, Wang, & Ooi, ). However, our hypothesized moderating influence of POC on the relationship between POS and AC should influence the indirect effect of POS on performance via AC (i.e., conditional indirect effect).…”
Section: Perceived Organizational Support and Affective Commitmentmentioning
confidence: 99%